Can Skills Training Programs Increase Employment for Young Women? : The Case of Liberia - World Bank (World Bank, Washington, DC, 2016)
Young people age 15 to 29 make up about a quarter of the world's population, yet they constitute nearly half of the world's unemployed. The World Bank is helping to increase viable employment opportunities for youth. In many countries, restrictive gender norms make it harder for girls to access training and employment opportunities. To ensure that girls and young women are included in this agenda, the Bank launched the Adolescent Girls Initiative (AGI) in 2008. The program is being piloted in eight low-income countries- including some of the toughest environments for girls. Each intervention is tailored to the country context, and includes an impact evaluation to build the evidence base to help adolescent girls and young women succeed in the labor market. The first AGI pilot- the Economic Empowerment of Adolescent Girls (EPAG) and young women project was launched in Liberia in late 2009. Preliminary results from the midline survey show that EPAG has been very successful in achieving its primary objectives- increasing employment and earnings among young women. The magnitude of the results is impressive when compared to findings from other youth training programs in developing countries. It is expected that successful economic empowerment programs like EPAG can also indirectly bring about positive behavioral changes and provide spillover benefits for the families and communities of trainees.